The dedicated spiritual life of Upper Rhine noble women a study and translation of a fourteenth-century spiritual biography of Gertrude Rickeldey of Ortenberg and Heilke of Staufenberg - Mulder-Bakker, Anneke B. 1940- (Sanctimoniales, 2017)
A study, edition, and translation of the story of two independent Upper Rhine women living a spiritual life together. Lady Gertrude Rickeldey of Ortenberg (d. 1335) was a noble widow who lived a spiritual, but secular life in her own household, first in Offenburg and later in Strasbourg, the economic and cultural heart of southern Germany. Her life story was written by a lay woman from Gertrude?s entourage and was based on numerous stories told by Gertrude's lifelong companion, Heilke of Staufenberg (d. after 1335). The biographer gives us a view of the aristocratic household, reports the many conversations that the women held with fellow believers and learned mendicants, and shows how they led a life of devotion in their own home, but at the same time, operated as full citizens of the city, taking part in both the civic and religious politics of Strasbourg. The details of her account reveal that the women did not take vows or renounce their possessions. They did not abandon their own decision-making power. Instead, they were mistresses of their own lives and developed into 'ethicae' of stature. Following historical investigations into Gertrude's and Heilke's life (Part I) is an edition and translation of the fourteenth-century text on which these studies are based (Part II)